Perubahan Perilaku Santri (Studi Kasus Alumni Pondok Pesantren Salafiyah di Desa Langkap Kecamatan Besuki Kabupaten Situbondo) - Happy Susanto; Muhammad Muzakki (ISTAWA, 2017)
Basically the students have been educated and guided by the cottage salafiyah with different habituation, that is by carrying out routine positive activities such as habituation discipline conducting worship obligatory, habituation implement devotions sunnah, habituation noble against teachers, parents and peers as well as away shameful and unjust deeds. But when they returned to their own villages phenomenon graduates of behavioral changes in santri who are not in accordance with the rules of Islam taught by the cottage salafiyah.  From this study we can conclude that Behavioral Changes Santri In Langkap Village District of Besuki Situbondo, as follows: (1) To instill the Islamic values to santri with sunnah worship, familiarize the santri disciplined in carrying out the obligatory worship, equip the santri with skills so that they are confident as to preach to the people, to familiarize the santri have a certain good for teachers, parents and friends. (2) The model of behavior change salafiyah alumni of the boarding school, namely; leaving habituation worship sunnah, dereliction of worship obligatory, not ashamed of female graduates open her nakedness, deeds are shameful and unjust. (3) Factors that cause changes of behavior salafiyah graduates of the boarding school, namely; there is a sense, not sincerely take part in boarding school finally  when returning home feel free to do anything, the environment of graduates santri was minimum in practice the teachings of Islam so that affects personality, economic pressure, lack of guidance and supervision of parents so that they are free to do anything, graduates age santri who are still teenagers so easily influenced by the environment, in short a vulnerable time in boarding school have an impact on self unsound science graduates santri.